Canine Anal Gland Affections and its Successful Surgico-Therapeutic Management - Parmar, Jignesh J; Shah, Aditya I; Patel, Shital K; Rao, Neha; Hadiya , Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A total 87 dogs, aged 2-15 years, presented at Veterinary Clinical Complex of the College in Anand with history of severe pain and straining during defecation, scooting, chronic diarrhea, anal gland fistula, maggot wound of anal glands, or tumour of anal glands were included in the study. Bilateral anal gland affections were highest followed by left side and right anal gland, in Labrador retriever followed by other breeds. The anal gland impaction was highest (36.78%) followed by abscess (32.18%), maggot infestation, fistula and tumours. Incidence was more in males (73.56%, 64/87) than in females (26.44% (23/87), and in age group of 2-10 years (85%). Among isolated bacteria from 61 samples of impacted materials and pus from the anal gland abscess Staphylococcus spp. (19) was the highest followed by Streptococcus spp. (18) and Gram-negative rods (18), Proteus spp. (4) and Klebsiella spp. (2). Ceftriaxone and amoxiclav were found most sensitive against Staphylococcus spp., and gentamicin against by Streptococcus spp. The dogs with different anal gland affections were treated with standard protocols including parenteral antibiotics according to sensitivity for five days. The mean values of TLC, neutrophils, and platelets count decreased significantly (p
Keywords: Anal gland abscess; Dog; Fistula; Impaction; Therapeutic management